A time error correction method based on virtual power for parallel simulation of power system. Issue 4 (15th March 2021) - Liu, Keyan; Meng, Xiaoli; Ye, Xueshun; Gong, Zhen; Kang, Wei; Kang, Zhongjian
Abstract: The simulation of complex power grid adopts the method of model segmentation. The system is divided into two or more subsystems. Each subsystem is calculated and solved in different computing units. Because the simulation model runs on different hardware, the time synchronization between subsystems may bring errors and stability problems. In this paper, a time synchronization method based on virtual power is proposed. It is assumed that there is a virtual load composed of resistance and inductance between different simulation subsystems, and two identical voltage sources are set at both terminals of the virtual load. When there is no time error between the subsystems, the power consumed by the virtual load should be zero, otherwise virtual power will be generated. The virtual power is sent to the PI regulator as the error signal, and the output of the regulator is used as the time error correction signal of the subsystem until the virtual power is zero, so as to realize the clock synchronization between multiple computers. In this paper, the theoretical analysis and implementation method of this time synchronization scheme are given in detail, and the simulation results show that the method is correct.